2015
DOI: 10.1080/02640414.2015.1014830
|View full text |Cite
|
Sign up to set email alerts
|

The use of spatial manipulation to examine goalkeepers’ anticipation

Abstract: This study investigated whether anticipation and search strategies of goalkeepers are influenced by temporally and spatially manipulated video of a penalty. Participants were clustered into three groups depending on skill: goalkeepers (n = 17), field players (n = 20) and control group (n = 20). An eye tracker was worn whilst watching 40 videos of a striker kicking to four corners of a goal in random order. All 40 videos were temporally occluded at foot-to-ball contact, and the non-kicking leg of 20 videos was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…This process highlighted a further eight papers that met the inclusion criteria and resulted in a total of 38 papers being included in this systematic review. Williams et al (1994); Davids (1997, 1998); Wood and Wilson (2010); Wood and Wilson (2011) When the eye remains in a stationary position for a period equal to or greater than 140ms Helsen and Starkes (1999) The period between the end of one saccade and the onset of the next saccade ; Williams et al (1994); Davids (1997, 1998); Wood and Wilson (2010); Woolley et al (2015) Mean number of fixations per second…”
Section: Resultsmentioning
confidence: 99%
“…This process highlighted a further eight papers that met the inclusion criteria and resulted in a total of 38 papers being included in this systematic review. Williams et al (1994); Davids (1997, 1998); Wood and Wilson (2010); Wood and Wilson (2011) When the eye remains in a stationary position for a period equal to or greater than 140ms Helsen and Starkes (1999) The period between the end of one saccade and the onset of the next saccade ; Williams et al (1994); Davids (1997, 1998); Wood and Wilson (2010); Woolley et al (2015) Mean number of fixations per second…”
Section: Resultsmentioning
confidence: 99%
“…In penalty 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w situations, the successful expert goalkeepers spend significantly more time looking at the non-kicking leg and waiting longer before responding to the kick [30]. However, Woolley et al [31] found that goalkeepers spent longer looking at the kicking foot and the ball at the point of final fixation. Kim and Lee [32] found that the difference in gaze behaviour between successful and unsuccessful penalty save occurred when goalkeepers fixated for a longer time on the approach phase of the kicker and not in the kick-swing phase.…”
Section: Technical Demandsmentioning
confidence: 97%
“…30 However, Woolley et al. 31 found that goalkeepers spent longer looking at the kicking foot and the ball at the point of final fixation. Kim and Lee 32 found that the difference in gaze behaviour between successful and unsuccessful penalty save occurred when goalkeepers fixated for a longer time on the approach phase of the kicker and not in the kick-swing phase.…”
Section: Technical Demandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring the different characteristics of expertise has required researchers to develop resourceful and inventive methodologies. Video simulations using occlusion techniques [6,11,12], pattern recall experiments [13] and laboratory-based experiments [14] are all examples of methods that have advanced our understanding of the various skills possessed by experts. However, an issue of ecological validity has been raised when using these methodologies [15,16].…”
Section: Introductionmentioning
confidence: 99%